2019
DOI: 10.1103/physreva.100.063622
|View full text |Cite
|
Sign up to set email alerts
|

Systematic effects in two-dimensional trapped matter-wave interferometers

Abstract: Trapped matter-wave interferometers (TMIs) present a platform for precision sensing within a compact apparatus, extending coherence time by repeated traversal of a confining potential. However, imperfections in this potential can introduce unwanted systematic effects, particularly when combined with errors in the associated beamsplitter operations. This can affect both the interferometer phase and visibility, and can make the performance more sensitive to other experimental imperfections. I examine the charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…The analysis described here is similar to that by West in Ref. [15]. However, in that work only a single interferometer was considered.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The analysis described here is similar to that by West in Ref. [15]. However, in that work only a single interferometer was considered.…”
Section: Introductionmentioning
confidence: 80%
“…However, in that work only a single interferometer was considered. By design, many errors cancel in the dual-interferometer scheme of [14], making our approach mainly sensitive to higherorder effects that were not comprehensively addressed in [15]. In addition, our numerical analysis considers a wider variety of perturbative parameters, including ones that couple all three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…该相位可由最后一步π/2型Ramsey干涉后读取自旋 上态的概率而测得. 终态中自旋上态概率理论值为 2019年, West [48] 在一个专门用于旋转传感的离子阱 系统物质波干涉仪中研究了这些系统效应, 发现对 势阱的良好控制可以使干涉仪不受实验缺陷的影 响. 同年, Urban等人 [49] 示范了在圆对称势下双离子 库仑晶体量子转子的相干控制.…”
Section: 根据Sagnac效应的基本原理 激光干涉仪或物 质波干涉仪累积的Sagnac相位可以表示为unclassified
“…In 2019, A. West [198] examined these systematic effects 093203-15 in a trapped ion-based matter-wave interferometer for rotation sensing in particular, and found that good control of the trapping potential can make interferometer insensitive to experimental imperfections. In the same year, E. Urban et al [199] demonstrated coherent control of quantum rotor of two-ion Coulomb crystal in a circularly symmetric potential.…”
Section: Ion-based Interferometermentioning
confidence: 99%